2017
DOI: 10.1080/13545701.2017.1404621
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Low-Paid Status, and Time Poverty in Urban China

Abstract: Using synthetic data from the 2008 China Time Use Survey (CTUS) and the 2008 China Household Income Project (CHIP), this study estimates timepoverty rates and compares the profiles of time-poor men and women workers in urban China. In line with previous research, time poverty is defined as a lack of enough time for rest and leisure. Three time-poverty measures are adopted. By all three measures, women paid workers and low-paid workers account for a disproportionate share of the time poor. Regression analysis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…The protecting of men's time lends further credence to scholars' arguments that time and time availability is a gendered practice (Beagan et al, ). The safeguarding of men's time rather than women's is also in line with research that has found women to be more “time poor” than men, meaning they do not have enough time for rest and leisure (Qi & Dong, , ). As Hochshild and Machung () note, men's time is seen as more valuable than women's, which leads to the notion that his leisure time is also more valuable, because it “enables him to refuel his energy, strengthen his ambition, and move ahead at work” (p. 247).…”
Section: Discussionsupporting
confidence: 73%
“…The protecting of men's time lends further credence to scholars' arguments that time and time availability is a gendered practice (Beagan et al, ). The safeguarding of men's time rather than women's is also in line with research that has found women to be more “time poor” than men, meaning they do not have enough time for rest and leisure (Qi & Dong, , ). As Hochshild and Machung () note, men's time is seen as more valuable than women's, which leads to the notion that his leisure time is also more valuable, because it “enables him to refuel his energy, strengthen his ambition, and move ahead at work” (p. 247).…”
Section: Discussionsupporting
confidence: 73%
“…People working in professions and industries that require longer working hours and provide low wages are more likely to be time poor. Qi and Dong (2018) emphasise the importance of wages in the analysis of time poverty in China. They estimate that female paid workers and low-paid workers account for an unequal percentage of the time poor population.…”
Section: Empirical Analysismentioning
confidence: 99%
“…However, another study using the same data focused on workers, and using a slightly similar definition of time poverty, reported a time poverty rate of 20% for weekdays and 22% for weekends (Chatzitheochari and Arber,2012). Qi and Dong (2018) found that 27.4% of the working population suffered from time poverty. Compared to the most recent measures, time poverty in Spain appears to be broadly similar to that of other developed countries.…”
Section: Time Povertymentioning
confidence: 99%
“…Women are at a disadvantage in this regard, as they tend to be more time-constrained than men due to their double burden of paid work and unpaid caregiving responsibilities. Studies suggest that female Chinese workers are more likely to be time-poor (lack of adequate time for rest and leisure) than male workers (Qi and Dong 2018), and that long work hours and time poverty are a significant correlate of poor mental health (Liu, MacPhail, and Dong 2018). Studies also find that time poverty is more prevalent among women with lower socioeconomic status, given that they often have to work longer hours to generate adequate incomes to meet their family's basic needs as their earnings are low; and they tend to spend more time on unpaid domestic and care work as their ability to outsource it to the market is more limited (Bardasi andWodon 2010, Qi and.…”
Section: Menmentioning
confidence: 99%